Transmedia Storytelling as a Cultural Industry Pacification Strategy of Generasi 90an Series - Patricia, Florens Debora (Wacana Seni Journal of Arts Discourse, 2026)
This pop series, Generasi 90an, is a nostalgic visual journal book featuring pop art illustrations that document Indonesia’s Generasi 90an nostalgic visual culture, utilising a transmedia storytelling approach to reinterpret nostalgic elements. The creative industry has also utilised this technology to manufacture distinctive, highly sought-after products continually. This study analyses the industrial motivations behind the transmedia reimagining of nostalgia in the Generasi 90an series. Transmedia storytelling functions not only as a strategy to increase fan involvement but also contributes to the cultural industry’s pacification as established by the Generasi 90an. The creator utilises transmedia storytelling to re-imagine, distort, and capitalise on the non-political aspects of 90s nostalgia, thereby bolstering their political influence. This approach maximises paratextual activities within interconnected narrative systems that are heavily influenced by modern digital technologies. As a result, contemporary capitalism is still utilising transmedia storytelling to develop iconic products and alternate realities within the digital era’s cultural industry, which caters to particular interests such as economic goals, political agendas, and socio-cultural objectives for the long-term viability of the capitalist system.